The influence of the reduction methods of the concrete hardening time on the parameters of the generated acoustic emission signal measured in plain and in high strength concretes - RANACHOWSKI, Z.; HOŁA, J.; POGAN, K. (Archives of Acoustics, 1999)
Results of the Acoustic Emission (AE) measurements including: AE counts sum, averaged AE event power and averaged AE events spectral pattern are presented in dependence on the concrete mixture type and on the used thermal treatment method. Six compositions differing in the compression strength were examined. Four of them were those of plain concrete and the remaining two were silica - fume modified compositions. The results let the authors to conclude that there is a correlation between the two AE signal parameters: the AE counts sum and the averaged AE events spectral pattern and the applied thermal treatment procedure and, further, that the nature of the so induced changes of the AE parameters is similar for all the six concrete compositions tested.